Ekonomi Analisis SWOT Infrastruktur Digital Publik (IDP) dalam Meningkatkan Inklusi Keuangan di Indonesia - Aprilia Dayini (STEI Kanjeng Sepuh Gresik Jawa Timur, 2024)
This study aims to determine Public Digital Infrastructure (IDP) in Increasing Financial Inclusion in Indonesia. This research method adopts a library research analysis technique, namely descriptive analysis plus qualitative analysis. Based on the SWOT (Strengths-Weaknesses-Opportunities-Threats) analysis of this study, it can be concluded that IDPs provide a basis for digital innovation. At the same time increasing productivity, encouraging financial transformation and inclusive economic growth, as well as providing easier and faster financial services for all. IDP Indonesia's development is supported by strong digital potential, and public digital infrastructure (IDP) plays an important role in supporting financial products that are conducive to increasing financial inclusion. Digitalization can increase productivity and resource efficiency.